2000
DOI: 10.1097/00000542-200008000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Desensitization of Human Mononuclear Cells after Cardiopulmonary Bypass

Abstract: Plasma contains interacting factors that inhibit the release of TNF-alpha and increase the release of IL-10, presumably attenuating the inflammatory response to CPB. Although norepinephrine fails to induce a cytokine response in the absence of other stimuli, its administration seems to augment the antiinflammatory IL-10 response while attenuating the TNF-alpha response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
1
7

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 1 publication
1
21
1
7
Order By: Relevance
“…In summary, TNF-a synthesis was independently influenced by the time of PBMNC isolation and sera preparation. synthesis of all measured pro-inflammatory cytokines and IL-10 serum levels, IL-10 alone cannot explain the inhibitory activity in patient sera after CPB, neither can monoclonal anti-IL-10 antibodies [15] nor complete absorption of IL-10 abolished TNF-a-inhibitory activity in patient sera after CPB [5]. As IL-10 is not released before aortic unclamping (in our study approximately 60 min.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In summary, TNF-a synthesis was independently influenced by the time of PBMNC isolation and sera preparation. synthesis of all measured pro-inflammatory cytokines and IL-10 serum levels, IL-10 alone cannot explain the inhibitory activity in patient sera after CPB, neither can monoclonal anti-IL-10 antibodies [15] nor complete absorption of IL-10 abolished TNF-a-inhibitory activity in patient sera after CPB [5]. As IL-10 is not released before aortic unclamping (in our study approximately 60 min.…”
Section: Discussioncontrasting
confidence: 55%
“…Recently it was demonstrated that TNF-a-inhibitory humoral activities are released after CPB [5,15]. Several stress-induced humoral mediators are increased after CPB, e. g. cortisol [16,17], prostaglandins (e. g. PGE 2 ) [18], soluble cytokine receptors [6] and anti-inflammatory cytokines [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After an initial systemic inflammatory response, major surgery (including cardiac surgery) leads to an anti-inflammatory state characterized by transient lymphocytopenia with impairment of T-cell activation and down-regulation of CD14 on monocytes. 15,43,44 When stimulated ex vivo, PBMCs and T lymphocytes obtained from such patients released less IFN-␥, shifting the balance from a Th-1 toward a Th-2 profile. This alteration can be (partially) reversed by the addition of IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the number and function of circulating immunocompetent cells have been reported after major surgery, reflecting some degree of "immune depression" [8,9]. Impairment of leukocyte functions essential for host defense, such as the ability to release oxygen free-radicals or to mount a cytokine response to bacterial stimuli, has been shown to correlate with an unfavourable postoperative outcome [5,23].…”
mentioning
confidence: 99%